Accuracy of hiatal hernia diagnosis in bariatric patients: Preoperative endoscopy versus intraoperative reference. Issue 6 (30th July 2020) - Chan, Daniel L; Wong, Simon K‐H; Lok, Hon Ting; Iliopoulos, Jim; Talbot, Michael L; Hennessy, Annemarie; Ng, Enders K‐W
Abstract: Background and Aim: Obesity is becoming increasingly prevalent in Asia. Bariatric surgery in the region is growing in popularity to reflect increasing demand. Hiatal hernia (HH) is common among the obese population. There is a lack of evidence comparing preoperative endoscopy against intraoperative findings as a standard of reference for HH diagnosis. Methods: This was a retrospective analysis of a bariatric procedure database from a single tertiary teaching hospital and high‐volume endoscopy center. Electronic medical records were reviewed. Endoscopy results were compared to intraoperative findings, and subgroup analysis of >2 cm hernias was performed. Sensitivity, specificity, predictive values, likelihood ratios, and global diagnostic test accuracy were calculated. Results: A total of 434 patients were eligible for this study, of which HH was detected in 37 patients (prevalence rate 8.55%). Mean age was 41.51 ± 11.07 years, and body mass index was 39.37 ± 5.67 kg/m 2 . Endoscopy sensitivity was 75.68% (95% confidence interval, 58.80–88.23%) and specificity 91.44% (88.24–94.00%). Positive likelihood ratio was 8.53 (6.11–12.79) and negative likelihood ratio 0.27 (0.15–0.47). Positive predictive value was 45.16% (36.27–54.38%) and negative predictive value 97.58% (95.80–98.62%). Accuracy of endoscopy for preoperative HH diagnosis was 90.09% (86.89–92.74%). Conclusion: Endoscopy can have a high diagnostic accuracy of preoperative HH diagnosis in obese Asian patients using intraoperative diagnosis as the reference standard. Abstract : This is a retrospective analysis of a bariatric procedure database, with endoscopy results compared to intraoperative findings. A total of 434 patients were eligible, of which hiatal hernia was detected in 37 patients (prevalence rate 8.55%). Endoscopy sensitivity was 75.68% and specificity 91.44%. Endoscopy can have high diagnostic accuracy (90.09%) for preoperative hiatal hernia diagnosis in obese Asian patients.